2012
DOI: 10.3892/ol.2012.895
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent prognostic factors and expression of GLUT-1, PI3K and p-Akt in adenoid cystic carcinomas of the head and neck: Clinicopathological features and biomarkers of adenoid cystic carcinoma

Abstract: Abstract. The purpose of this study was to explore the factors associated with the recurrence of adenoid cystic carcinomas (ACCs). We examined the recurrence values of clinicopathological variables and GLUT-1, p-Akt and PI3K expression in 42 patients with ACC. Of the 42 patients, 17 developed recurrence following initial surgery. The positive rates of GLUT-1, PI3K and p-Akt protein expression in ACC were 38.1, 38.1 and 50.0%, respectively. The expression of GLUT-1, p-Akt or PI3K protein in ACC was higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Furthermore, a recent study reported that SOX2, Slug and ALDH are overexpressed in human head and neck cancer [30][31][32][33]. Our result indicated that a close association between SOX2, Slug, ALDH1 and ME2.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, a recent study reported that SOX2, Slug and ALDH are overexpressed in human head and neck cancer [30][31][32][33]. Our result indicated that a close association between SOX2, Slug, ALDH1 and ME2.…”
Section: Discussionsupporting
confidence: 67%
“…Significant correlations between GLUT-1 and PI3K expression (r=0.394, p=0.01), between GLUT-1 and p-Akt expression (r=0.528, P<0.001), and between p-Akt and PI3K expression (r=0.528, P<0.001) were also observed. In this study, a multivariate analysis showed that p-Akt was a significant predictor of recurrence and that GLUT-1 expression was associated with T stage (according to the TNM classification) and distant metastasis of ACC (118). In a ceruminous adenoma of the external auditory canal, it was also shown by immunohistochemistry that tumor cells were positive for GLUT-1, HIF-1, PI3K and p-Akt (119).…”
Section: Association Between Glut-1 and Pi3k/aktmentioning
confidence: 53%
“…GLUT-1 overexpression enables the transport of increased levels of glucose to fulfil the high metabolic rate and rapid growth requirements of malignant cells. In our previous study, it was demonstrated that overexpression of GLUT-1 may have a role in the development of recurrence of ACC-2 cells ( 2 ). In addition, GLUT-1 has been suggested as a potential therapeutic target in other types of cancer ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%